Oxidative stress in the brain is regulated by social status in a highly social cichlid fish - Dijkstra, Peter D.; Fialkowski, Robert J.; Bush, Brady; Wong, Ryan Y.; Moore, Travis I.; Harvey, Ashley R. (Frontiers in Behavioral Neuroscience, 2024)
Social stress can increase reactive oxygen species and derail antioxidant function in the brain, which may contribute to the onset and progression of mental health disorders. In hierarchical species, repeated social defeat can raise oxidative stress in the brain. However, how oxidative balance in the brain is regulated across different levels in a social hierarchy is unknown. Here, we study the effect of social status on patterns of oxidative stress across several brain divisions in a highly social cichlid fish, Astatotilapia burtoni. In this species, dominant males are territorial, brightly colored, and reproductively active while subordinate males are not. We measured several markers of oxidative stress in macrodissected brain divisions in dominant and subordinate males. We found that dominant individuals had lower oxidative DNA damage (8-OhdG) in the midbrain while also having increased total antioxidant capacity in the midbrain and hypothalamus. However, in dominant males, oxidative DNA damage tended to be higher in the hypothalamus while total glutathione levels were lower in the telencephalon compared to subordinate males. Finally, we found that indicators of reproductive activity (gonadosomatic index and social behavior) were coregulated with antioxidant function or oxidative damage in the telencephalon.Combined, our results suggest that social status and activation of the reproductive system regulate oxidative balance in the brain in a highly brain division specific manner.